Advances in Magnesium Injection Molding (Thixomolding) - Scharrer, Martin; Lohmüller, Andreas; Hilbinger, Rolf Michael; Eibisch, Harald; Jenning, Ralf; Hartmann, Mark; Singer, Robert (Proc. of 7th International Conference Magnesium Alloys and Their Applications, 2006)

Advances in Magnesium Thixomolding - Lohmüller, Andreas; Scharrer, Martin; Jenning, Ralf; Rauber, Christian; Loos, Michael; Kömpel, Natalie; Hilbinger, Rolf Michael; Hartmann, Mark; Singer, Robert (15th Automotive and User Seminar, 2007)

Approaching series production of light weight components by Magnesium Injection Molding - Volek, Andreas; Lohmüller, Andreas; Bräutigam, Volker; Grimm, Michael; Hilbinger, Rolf Michael; Hartmann, Mark; Otten, H.; Singer, Robert (16th Magnesium Automotive and User Seminar, 2008)

Fabrication and properties of syntactic magnesium foams - Hartmann, Mark; Reindel, Klaus; Singer, Robert (Proceedings of the 1998 MRS Spring Symposium, 1998)

Herstellung, Struktur und Eigenschaften syntaktischer Magnesiumschäume - Hartmann, Mark (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2015)

Herstellung und Eigenschaften syntaktischer Magnesiumschäume - Hartmann, Mark; Singer, Robert (Metallschäume, 1997)

Herstellung und Eigenschaften von Kohlenstofflangfaser verstärktem Magnesium im Druckguss - Eibisch, Harald; Hartmann, Mark; Singer, Robert (3. Ranshofer Leichtmetalltage 2004, 2004)

Herstellung von partikelverstärkten Verbundwerkstoffen durch Magnesiumspritzgießen - Rauber, Christian; Lohmüller, Andreas; Hilbinger, Rolf Michael; Opel, Simon; Hartmann, Mark; Singer, Robert (17. Symposium Verbundwerkstoffe und Werkstoffverbunde, 2009)

Injection Molding of Magnesium Alloys - Lohmüller, Andreas; Scharrer, Martin; Jenning, Ralf; Hilbinger, Rolf Michael; Hartmann, Mark; Singer, Robert (Proceedings of the 6th International Conference Magnesium Alloys and Their Applications, 2004)
UnivIS-Import:2015-04-16:Pub.2004.tech.IW.LWWTM.inject

Kupferdampflaser für die Mikromaterialbearbeitung - Bergmann, Hans Wilhelm; Hartmann, Mark; Mayerhofer, Roland; Körner, Carolin (Laser '95, 1995)

Microstructure and Mechanical Properties of Cellular Magnesium Matrix Composites - Hartmann, Mark; Crößmann, Inga; Reindel, Klaus; Singer, Robert (Metal Foams and Porous Metal Structures, 1999)

Physical and material aspects in using visible laser pulses of nanosecond duration for ablation - Körner, Carolin; Mayerhofer, Roland; Hartmann, Mark; Bergmann, Hans Wilhelm (Applied Physics A-Materials Science & Processing, 1996)
Interaction phenomena of 50 ns copper vapour laser pulses (λ = 511/578 nm) with matter are investigated. The basic ablation process is classified into four fundamental classes. On basis of this classification processing results are connected with specific material properties like the brittleness, the viscosity of the melt or the optical properties. Knowing these properties a prognosis of the expected fundamental process is possible. In order to generate a geometrically defined structure via ablation in a given material-specific process, strategies have to be developed. Typical examples for process strategies are given.

Precision machining with copper vapour lasers - Bergmann, Hans Wilhelm; Körner, Carolin; Hartmann, Mark; Mayerhofer, Roland (NATO Proc. Advanced Workshop, Pulsed Metal Vapor Lasers, 1996)
In the present paper criteria are presented for precision machining with laser beams. It is outlined that a copper vapour laser system (CVL) consisting of an unstable resonator, subsequent amplifiers, a suitable synchronizing unit, an optical system for beam forming and guiding and an CNC-handling system fulfills most of these requirements. Machining speeds are given for different materials. Finally, examples are shown for possible applications of CVL-processing.

Reinforced Light Metals for Automotive Applications - Bechmann, Florian; Fallböhmer, Peter; Stauber, Rudolf; Rauber, Christian; Lohmüller, Andreas; Hartmann, Mark; Singer, Robert (SAE International 2007 World Congress, 2007)

Thixospritzgiessen von Magnesiumlegierungen - Lohmüller, Andreas; Scharrer, Martin; Hilbinger, Rolf Michael; Jenning, Ralf; Hartmann, Mark; Singer, Robert (Gießereiforschung, 2005)

Vermeidung von Gussfehlern - Prognose von Eigenschaften durch Modellierung - Hilbinger, Rolf Michael; Köpf, Johannes; Lohmüller, Andreas; Scharrer, Martin; Hartmann, Mark; Singer, Robert (Druckguss, 2005)